Avaliação da sexualidade do binômio paciente com doença pulmonar obstrutiva crônica / cuidador primário e seus fatores associados - Macêdo, Tereza Efigênia Pessoa Morano (2018)
Background: The sexual problems (male and female sexual dysfunctions, development difficulties and sexual satisfaction) are turned into a relevant situation of public health that involvepart of the population and prejudge the quality of life. Objective: Evaluate the sexuality of the binomial COPD patient and its primary caregiver and associated factors. Casuistic and Method: Descriptive, transversal, multicenter and quantitative study. The participants were the patients and their caregivers. The following data aspects evaluated the patient: sociodemographic, clinic, spirometry and 6min walk test. Applied tests: Medical Research Council (mMRC) for dyspnea evaluation, SF-36 (Short form – 36) for life quality evaluation, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), male sexual quotient scale (QS-M) and female sexual quotient scale (QS-F).Results: Among the 52 patients, 54% (28/52) women and 61% (32/52) married. The mean age 71, 1±10 years. Among the 52 caregivers, 87% (45/52) women, 48% patient‟s daughters. The mean age 49 ± 15, 1 years. The patient sexuality percentage for bad/unfavorable pattern prevailed with 82% (43/52). Comparing this result with the regular/excellent pattern, patients with the worst sexuality pattern presented bad quality of life in the Short form – 36 (SF-36), Mental CoefficientSummarized (MCS)(44,97 ± 13,67 vs 59,12 ± 13,45; p = 0,007). It was also observed high anxiety and depression levels between the patients with null-unfavorablevs regular-excellent sexuality pattern (16,05 ± 11,19 vs 7,2 ± 7,0; p= 0,02 e 18,70 ± 9,11 vs 10,67 ± 8,17; p = 0,01). In the multivariate analysis, patients with higher depression levels showed a chance of 1, 13 (IC 95% 1, 02 - 1, 25) of presenting a null-unfavorable sexual development. Among the caregivers, the null-unfavorable sexuality pattern describes 5% (9/52). These caregivers showed worst life quality comparing those with regular-excellent, in both MCS and Physical Coefficient Summarized (PCS) from SF-36(MCS = 41,19 ± 14,36 vs 49,21 ± 11,38, p = 0,02; PCS = 41,12 ± 10,98 vs47,15 ± 9,57, p = 0,04, respectively).Also greater depression levels (median 12,9, IQ = 8,50 - 15,5 vs median6,27, IQ = 1,00 - 9,00, p = 0,007, respectively) and were older (57,41 ± 14,03 vs 42,97 ± 13,12, p = 0,001 respectively). In the multivariate analysis, caregivers with higher depression levels and older showed 10 a greater chance of presenting a null-unfavorable sexual development [1, 11 (IC 95% 1, 02 - 1, 25) e 1, 08 (IC 95% 1, 02 - 1, 14)], respectively]. Conclusion: Among the patients prevailed the null-unfavorable sexuality pattern. Patients with higher depression level showed low sexual development. Moreover, between the caregivers, the oldest oneswith a greater depression level showed low sexual development. Key words:sexuality, Chronic Obstructive Pulmonary Disease (COPD), COPD patient / primary caregiver binomial, life quality (LQ), anxiety, depression